Experimental studies of electron affinity and work function from titanium on oxidised diamond (100) surfaces. Issue 1 (31st December 2022) - Fogarty, Fabian; Fox, Neil A.; May, Paul W.
Abstract: Sub-monolayers of titanium were deposited onto oxidised (100) single-crystal diamond surfaces and annealed in vacuo at temperatures up to 1000 °C to find a temperature-stable termination procedure that produces a surface with Negative Electron Affinity (NEA). The samples were analysed by X-ray Photoelectron Spectroscopy, Ultraviolet Photoelectron Spectroscopy and Energy-Filtered Photoemission Electron Microscopy to determine their electron affinity and work function values. NEA values were observed on samples following annealing above 400 °C, with the largest NEA value being –0.9 eV for a sample coated with a half-monolayer of Ti annealed at 400 °C. Work function values were ∼4.5 eV for all samples annealed at temperatures between 400 and 600 °C, then rose at higher temperatures due to the loss of substantial amounts of O from the surface. Work-function maps indicated that the surface was uniform over areas 5700 μm 2, suggesting that the deposition and annealing steps used are reliable methods to produce films with homogeneous surface properties. Graphical Abstract: UF0001